2005
DOI: 10.1111/j.1365-246x.2005.02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-reversal of remanent magnetization in basalts due to partially oxidized titanomagnetites

Abstract: S U M M A R YA range of basaltic samples from Olby (France) and Vogelsberg (Germany) displaying the phenomenon of partial and complete self-reversal was studied in order to decipher the physical mechanism responsible for self-reversed magnetic remanence in basalts. Microscopic observations and rock magnetic measurements show titanomagnetite to be the carrier of remanence. Due to low-temperature oxidation the titanomagnetites are present in two magnetic phases forming close side-by-side phase assemblages: The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 58 publications
(105 reference statements)
5
51
2
Order By: Relevance
“…[25] It has long been known that self-reversal of thermoremanence could be caused by negative magnetic coupling between two phases [e.g., Havard and Lewis, 1965;Tucker and O'Reilly, 1980;Heller and Petersen, 1982;Krása et al, 2005]. Our rock magnetic analyses indicate there are at least two magnetic phases existing in samples heated to temperatures between 300 and 500°C, e.g., the higher T c Ti-poor phase (magnetite) and the lower T c Ti-rich ATM phase.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…[25] It has long been known that self-reversal of thermoremanence could be caused by negative magnetic coupling between two phases [e.g., Havard and Lewis, 1965;Tucker and O'Reilly, 1980;Heller and Petersen, 1982;Krása et al, 2005]. Our rock magnetic analyses indicate there are at least two magnetic phases existing in samples heated to temperatures between 300 and 500°C, e.g., the higher T c Ti-poor phase (magnetite) and the lower T c Ti-rich ATM phase.…”
Section: Discussionmentioning
confidence: 85%
“…The phase interaction (e.g., negative magnetic couplings) may cause the observed pTRM acquisition decrease with elevated treatment temperatures. Krása et al [2005] observed the influence of oxidation on the domain configuration using a magnetic force microscopy and found that the two magnetically coupled phases lead to the lower T c phase acquiring a TRM in a direction antiparallel to the applied external magnetic field. Their numerical modeling indicated that the domain configuration is capable of causing partial and complete self-reversal due to phase coupling of the two phases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A goal of the work was to find and identify the low-temperature oxidized Ti-Mgh -disordered-antiferromagnetic phase. The self-reversed origin of reversed RM of submarine basalts was revealed also by Doubrovine and Tarduno (2004), in basalts also by Krása et al (2005), also by Pan et al (2006). I have been studying the literature concerning the problem of the reversed RM bearing volcanics and the sedimentary rocks.…”
Section: Discussionmentioning
confidence: 99%